Studi Komunitas Padang Lamun di Kecamatan Tanggetada, Kabupaten Kolaka, Sulawesi Tenggara - Ilham Antariksa Tasabaramo; Riska Riska; Petrus C. Makatipu; Aditya Hikmah Nugraha; Hasan Eldin Adimu (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
Tanggetada District has a large area of seagrass beds and is often used by the community. Seagrass beds in this area have not been scientifically confirmed, both in terms of species, density and seagrass communities. This study aims to determine the type and density of seagrass in Tanggetada District. The method used in this study is a quadratic transect method in an area of 100 m2 at each station. The location of the research was carried out at 3 stations, namely Station 1 in Tanggetada Village, Station 2 in Palewai Village and Station 3 in Anaiwoi Village. The results showed that 6 species of seagrass were found in Tanggetada District, namely Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, Halodule uninervis, Halophila ovalis, and Syringodium isoetifolium. Seagrass density is included in the category of dense and rare. Station 1 has a high density of seagrass with a dense category of 160.46 ind/m2, then Station 2 with a rather dense seagrass density of 117.49 ind/m2 and Station 3 with a low density of seagrass with a rare category of 60.59 ind/m2. Thalassia Hempricii is a seagrass that has the highest density value compared to other seagrass speciesseagrass density in the rare category. Thalassia Hempricii is a seagrass that has the highest density value compared to other seagrass species.